2017
DOI: 10.1200/jco.2017.35.15_suppl.11064
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of histo-pathological diagnosis of patients with soft tissue sarcoma referred to tertiary care center.

Abstract: 11064 Background: Reaching to the correct histo-pathological diagnosis of soft tissue sarcomas (STS) is a great challenge and is cornerstone for treatment planning. Need of expertise for diagnosis is limited by lack of expert pathologists and dedicated sarcoma oncologists in India. Through this study we highlight the pattern of pathological diagnosis and accuracy outside specialist centre. Methods: We did retrospective analysis of all patients referred to us with diagnosis of STS in the last 12 months (Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our findings are in accordance with previous reports. The importance of second opinion in sarcoma diagnostics has been recognized since more than 30 years ago [13][14][15]22,31]. A population-based study within 3 European regions, which analyzed retrospectively 1463 sarcoma patients, revealed a modification in diagnosis in more than 40% of cases as a result of a centralized expert pathology review [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in accordance with previous reports. The importance of second opinion in sarcoma diagnostics has been recognized since more than 30 years ago [13][14][15]22,31]. A population-based study within 3 European regions, which analyzed retrospectively 1463 sarcoma patients, revealed a modification in diagnosis in more than 40% of cases as a result of a centralized expert pathology review [16].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis is crucial for patients' management to enable a histology-tailored approach, as recommended both in surgery [11] and systemic therapy for sarcomas [12], requiring, thus, an expert pathologist. There is a number of studies that have demonstrated a rate of discrepancy between initial and expert diagnosis in sarcoma up to 50% [13][14][15][16][17][18][19][20][21], whereas the effect of pathology review on management has scarcely been investigated [19]. These studies took place mainly in USA and Europe, with some recent reports also from India [15], Australia [19] and Canada [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There can be a delay in diagnosis of such rare tumours, as in our patient. Since KH is a rare tumor, the delay may be due to lack of expert sarcoma pathologist and dedicated sarcoma oncologists in India [ 24 ]. More collaboration between different specialists like surgery, orthopaedics, radiology and pathology is required for streamlining and optimizing patient management.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoma is a kind of malignant tumor, which can be classi ed into bone sarcomas and soft tissue sarcomas based on the tumor-of-origin. The overall 5year survival for bone sarcomas and soft tissue sarcomas are 66.9% and 64.5% [23,24].…”
Section: Introductionmentioning
confidence: 99%